A case series of immune checkpoint inhibitor-induced gastritis - Karavasili, Athanasia; Yerolatsite, Melina; Zarkavelis, George; Karafousia, Vaia; Torounidou, Nanteznta; Amylidi, Anna-Lea; Kampletsas, Eleftherios (Contemporary Oncology/Współczesna Onkologia, 2025)
Immune checkpoint inhibitors (ICIs) have become a cornerstone in the treatment of various solid tumors due to their proven efficacy. However, their use is associated with immune-related adverse events (irAEs), which arise from the immune response activated by ICIs. Gastrointestinal irAEs are among the most common and often present as diarrhea or colitis, conditions that can sometimes require discontinuation of ICI therapy. Although irAE gastritis is less frequently reported, it can lead to severe complications, such as gastrorrhagia. Diagnosing immune-related gastritis early can be challenging due to its diverse clinical presentations. While glucocorticoids and other immunosuppressive therapies are standard treatments for irAEs, the optimal management strategy and dosing for immune-related gastritis remain unclear. This case series on gastritis caused by ICI therapy aims to provide clinicians with valuable insights into this complex condition and its management.